PENGARUH LINGKUNGAN KERJA, TOTAL QUALITY MANAGEMENT, DAN REWARD TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. DITIANASAR SARANA ABADI - Azzahra, Tiara Raihanah (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study’s main objective, is to determine the influence of the Work Environment, Total Quality Management (TQM), and Rewards on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Ditianasar Sarana Abadi using a quantitative descriptive approach. This study used saturated samples. The population and sample of this study were 78 employees at PT. Ditianasar Sarana Abadi. Data analysis in this study used the SmartPLS 3.0 software analysis tool for the data collection method, namely using the questionnaire method for data collection. The results of this study show that the variables of the work environment do not have a significant positive effect on employee performance, total quality management (TQM) does not have a significant positive effect on employee performance, reward has a significant positive effect on employee performance, job satisfaction has a significant positive effect on employee performance, the work environment has a significant positive effect on job satisfaction, total quality management (TQM) has a significant positive effect on job satisfaction, reward has a significant positive effect on job satisfaction, work environment has a significant positive effect on employee performance with job satisfaction, total quality management (TQM) /has a significant positive effect on employee performance with job satisfaction, reward has a significant positive effect on employee performance with job satisfaction.